Ferdinand Christian Baur and the history of early christianity - Bauspieß, Martin 1977-; Landmesser, Christof 1959-; Lincicum, David 1979-; Brown, Robert F.; Hodgson, Peter Crafts 1934-; Baur, Ferdinand Christian 1792-1860 (Oxford Oxford University Press, 2017)
"Ferdinand Christian Baur (1792-1860) has been described as 'the greatest and at the same time the most controversial theologian in German Protestant theology since Schleiermacher.' The controversy was epitomized by a nineteenth-century British critic who wrote that his theory "makes of Christianity a thing of purely natural origin, calls in question the authenticity of all but a few of the New Testament books, and makes the whole collection contain not a harmonious system of divine truth, but a confused mass of merely human and contradictory opinions as to the nature of the Christian religion." The contributors to this volume, however, regard Baur as an epoch-making New Testament scholar whose methods and conclusions, though superseded, have been mostly affirmed during the century and a half since his death. This collection focuses on the history of early Christianity, although as a historian of the church and theology Baur covered the entire field up to own time. He combined the most exacting historical research with a theological interpretation of history influenced by Kant, Schelling, and Hegel. The first three chapters discuss Baur's relation to Strauss, Mohler, and Hegel. 0Then a central core of chapters considers his historical and exegetical perspectives (Judaism and Hellenism, Gnosticism, New Testament introduction and theology, the Pauline epistles, the Synoptic Gospels, John, the critique of miracle, and the combination of absoluteness and relativity). The final chapters view his influence by analyzing the reception of Baur in Britain, Baur and Harnack, and Baur and practical theology. This work offers a multi-faceted picture of his thinking, which will stimulate contemporary discussion.:--Back cover
Part 1: Connections and demarcations. Ferdinand Christian Baur and David Friedrich Strauss / Ulrich Köpf ; Ethical judgment and ecclesiastical self-understanding: Ferdinand Christian Baur's interpretation of the Protestant principle in the controversy with Johann Adam Möhler / Notger Slenczka ; Ferdinand Christian Baur: a historically informed idealist of a distinctive kind / Martin Wendte -- Part II: Historical and exegetical perspectives. Ferdinand Christian Baur and the theological task of New Testament introduction / David Lincicum ; Baur and the creation of the Judaism-Hellenism dichotomy / Anders Gerdmar ; Ferdinand Christian Baur's view of Christian gnosis, and of the philosophy of religion in his own day / Volker Henning Drecoll ; Ferdinand Christian Baur as interpreter of Paul: history, the absolute, and freedom / Christof Landmesser ; The essence of Early Christianity: on Ferdinand Christian Baur's view of the Synoptic Gospels / Martin Bauspiess ; Ferdinand Christian Baur and the interpretation of John / Jörg Frey ; F. C. Baur's New Testament theology / Robert Morgan ; Belief in miracles as the gateway to atheism: theological-historical remarks about Ferdinand Christian Baur's critique of miracles / Stefan Alkier ; The absoluteness of Christianity and the relativity of all history: two strands in Ferdinand Christian Baur's thought / Johannes Zachhuber -- Part III: Influences. The reception of Baur in Britain / James Carleton Paget ; The similarity of the two masters: Ferdinand Christian Baur and Adolf von Harnack / Daniel Geese ; Ferdinand Christian Baur and practical theology / Birgit Weyel
Keywords: Baur, Ferdinand Christian -- 1792-1860; Bible -- Criticism, interpretation, etc -- History; Church History -- Primitive and early church, ca. 30-600; Aufsatzsammlung